Attention, representation, and human performance : integration of cognition, emotion, and motivation - Masmoudi, Slim.; Dai, David Yun.; Naceur, Abdelmajid (New York : Psychology Press, 2012)
'This volume presents a rare occasion where scholars from Europe, North Africa and North America share their research programs and findings revolving around an important theme: integration. Despite different research foci and methodologies, there is a strong consensus that we need to understand a psychological phenomenon in all its complexity, involving its neural, psychological, and social dimensions, involving perception and conception, and decision processes, involving motivation, emotion, and cognition -- all in complex interaction. This volume is intended to reach out to basic and applied psychological researchers, cognitive and affective scientists, learning scientists, biologists, sociologists, neuropsychological researchers, and philosophers, who have an interest in an integrated understanding of the mind at work, particularly pertaining to explanations of real-life phenomena that have social and practical significance. A distinct feature of this volume is that most research involved is heavily built on neuropsychological evidence, while loyal to the experimental tradition with its focus on functional behavior in various situations and conditions that mimic or resemble real life. The viability of this approach to doing cutting-edge research that is relevant and applicable to many real-life phenomena should also make this body of research useful for a wide range of human endeavor, from religion, education, to industrial and organizational psychology'--
Includes bibliographical references and index.
Keywords: Cognitive psychology; Emotions and cognition; Motivation (Psychology).; Cognition